2013
DOI: 10.1080/09603123.2012.755152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indoor air contaminants in a randomly selected set of commercial nail salons in Salt Lake County, Utah, USA

Abstract: Air samples were collected in 12 randomly selected commercial nail salons in Salt Lake County, Utah. Measurements of salon physical/chemical parameters (room volume, CO2 levels) were obtained. Volatile organic compound (VOC) concentrations were collected using summa air canisters and sorbent media tubes for an 8-h period. Multivariate analyses were used to identify relationships between salon physical/chemical characteristics and the VOCs found in the air samples. The ACGIH(®) additive mixing formula was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 10 publications
6
36
0
Order By: Relevance
“…Nevertheless, median airborne levels of all the investigated VOC were far below the TLVs obligatory in Poland and none of the 109 nail salons enrolled in our study was seen to exceed the Polish TLV for any of the measured chemicals. It has to be, however, stated that even though the median and maximum values of total amount of airborne VOC found in our study (17.1 mg/m 3 and 139.4 mg/m 3 , respectively) were consistent with those reported in a recent study by Goldin et al (11 mg/m 3 and 87 mg/m 3 , respectively) (44), the direct comparison of airborne levels of individual VOC in nail salons among different studies is difficult, mainly due to a huge degree of variability of published data and different measures of centrality used by various authors (arithmetic/geometric means, median) (31,32,(41)(42)(43). Either way, median and maximum airborne levels of acetone, 2-butanone, isopropyl alcohol, hexamethyld- Figure 1.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, median airborne levels of all the investigated VOC were far below the TLVs obligatory in Poland and none of the 109 nail salons enrolled in our study was seen to exceed the Polish TLV for any of the measured chemicals. It has to be, however, stated that even though the median and maximum values of total amount of airborne VOC found in our study (17.1 mg/m 3 and 139.4 mg/m 3 , respectively) were consistent with those reported in a recent study by Goldin et al (11 mg/m 3 and 87 mg/m 3 , respectively) (44), the direct comparison of airborne levels of individual VOC in nail salons among different studies is difficult, mainly due to a huge degree of variability of published data and different measures of centrality used by various authors (arithmetic/geometric means, median) (31,32,(41)(42)(43). Either way, median and maximum airborne levels of acetone, 2-butanone, isopropyl alcohol, hexamethyld- Figure 1.…”
Section: Discussionsupporting
confidence: 76%
“…The VOC most frequently detected in nail salon air samples were acetone, ethanol, toluene, 2-propanol, 2-butanone, ethyl acetate and n-butyl acetate (all of them in >90% of all samples), in contrast to EMA and MMA, which were found in only 51% and 18% of analyzed air samples, respectively. Similar low frequencies of EMA, MMA or both were reported by the majority of previous studies even though the subjects involved in these studies reported an almost exclusive employment of the EMA/MMA-involving techniques of artificial nail sculpturing during their work time (31,32,(41)(42)(43). It is thus possible that besides techniques employed, other factors (such as ventilation, EMA/MMA content in used nail products, etc) not involved in any of these studies, may influence the resultant relative airborne levels of EMA or MMA.…”
Section: Discussionsupporting
confidence: 61%
“…Nail products such as nail polish or nail polish remover can emit various VOCs including benzene or toluene, and cause significant exposure in conditions lacking efficient ventilation [23,34]. Other cosmetics like perfumes, washing agents, and hair dyes contain benzyl alcohol, which is metabolized into benzoic acid and derives hippuric acid [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Although methyl methacrylate compounds are reportedly banned in nail products in Utah, 58% of facilities had detectable levels in the air [112]. 58% of establishments also had detectable formaldehyde above the recommended exposure limits set by the National Institute for Occupational Safety and Health in the US (> 0.016 parts per million (ppm)) [112]. A study of air in Californian salons revealed that measured values of isopropyl alcohol and ethyl acetate were within the California Division of Occupational Safety and Health's occupational limits.…”
Section: Occupational Exposurementioning
confidence: 99%
“…For instance, 12 randomly-selected nail salons in Salt Lake City, Utah, US were analyzed for the concentration of volatile organic compounds in the facilities. Although methyl methacrylate compounds are reportedly banned in nail products in Utah, 58% of facilities had detectable levels in the air [112]. 58% of establishments also had detectable formaldehyde above the recommended exposure limits set by the National Institute for Occupational Safety and Health in the US (> 0.016 parts per million (ppm)) [112].…”
Section: Occupational Exposurementioning
confidence: 99%